Microstructure, Shape Memory Effect and Functional Stability of Ti67Ta33 Thin Films1. Issue 10 (27th February 2015) - Motemani, Yahya; Kadletz, Peter M.; Maier, Bernd; Rynko, Ramona; Somsen, Christoph; Paulsen, Alexander; Frenzel, Jan; Schmahl, Wolfgang W.; Eggeler, Gunther; Ludwig, Alfred
<x xml:space="preserve">Abstract</x> Ti–Ta based alloys are an interesting class of high‐temperature shape memory materials. When fabricated as thin films, they can be used as high‐temperature micro‐actuators with operation temperatures exceeding 100 °C. In this study, microstructure, shape memory effect and thermal cycling stability of room‐temperature sputter deposited Ti67Ta33 thin films are investigated. A disordered α″ martensite (orthorhombic) phase is formed in the as‐deposited Ti67Ta33 films. The films show a columnar morphology with the columns being oriented perpendicular to the substrate surface. They are approximately 200 nm in width. XRD texture analysis reveals a martensite fiber texture with {120} and {102} fiber axes. The XRD results are confirmed by TEM analysis, which also shows columnar grains with long axes perpendicular to the {120} and {102} planes of α″ martensite. The shape memory effect is analyzed in the temperature range of –10 to 240 °C using the cantilever deflection method, with special emphasis placed on cyclic stability. Ti67Ta33 thin films undergo a forward martensitic transformation at Ms ≈ 165 °C, with a stress relaxation of approximately 33 MPa during the transformation. The actuation response of the film actuators degrades significantly during thermal cycling. TEM analysis shows that this degradation is related to the formation of nanoscale ω precipitates (5–13 nm) which form above the austenite finish temperature. These precipitates suppress the martensitic transformation, as they act as obstacles for the growth of martensite variants.